Islamic social funds to foster yunusian social business and conventional social enterprises - Reazul Islam; Mustaffa Omar; Mahfuzur Rahman (Administrative Sciences, 2023)
This paper proposes an integrated, comprehensive financial model that can provide startup capital to socially committed business ventures, such as social enterprises and Yunus Social Business (YSB), by using Islamic social funds (ISFs), Zakat (almsgiving), Waqf (endowments), Sadaqat (charity), and Qard Hasan (interest-free benevolent loans). The literature review method was adopted to explain this model's architecture, applications, implications, and viability. On the basis of logical reasoning, it concludes that ISFs can yield greater social wellbeing if utilised in SEs and YSB than in unconditional charity because both business models work for social betterment in entrepreneurial ways while remaining operationally self-reliant and economically sustainable. Additionally, ISFs can complement Yunus Social Business's zero-return investment approach to make it more robust towards social contributions. The implementation of the model orchestrated in this paper would enhance societal business practices and, hence, scale up social wellbeing while helping rejuvenate pandemic-stricken economies. It paves the way for new research too.
Keywords: 350; COVID-19; Islamic social funds; social enterprise; value-based intermediation; Yunus Social Business